Arabidopsis cargo receptor NBR1 mediates selective autophagy of defective proteins. (8th September 2019) - Jung, Hyera; Lee, Han Nim; Marshall, Richard S; Lomax, Aaron W; Yoon, Min Ji; Kim, Jimi; Kim, Jeong Hun; Vierstra, Richard D; Chung, Taijoon
Abstract : Arabidopsis cargo receptor NBR1 contributes to protein quality control by promoting the formation of protein aggregates and mediating their clearance via selective autophagy. Abstract: Aggrephagy, a type of selective autophagy that sequesters protein aggregates for degradation in the vacuole, is an important protein quality control mechanism, particularly during cell stress. In mammalian cells, aggrephagy and several other forms of selective autophagy are mediated by dedicated cargo receptors such as NEIGHBOR OF BRCA1 (NBR1). Although plant NBR1 homologs have been linked to selective autophagy during biotic stress, it remains unclear how they impact selective autophagy under non-stressed and abiotic stress conditions. Through microscopic and biochemical analysis of nbr1 mutants expressing autophagy markers and an aggregation-prone reporter, we tested the connection between NBR1 and aggrephagy in Arabidopsis. Although NBR1 is not essential for general autophagy, or for the selective clearance of peroxisomes, mitochondria, or the ER, we found that NBR1 is required for the heat-induced formation of autophagic vesicles. Moreover, cytoplasmic puncta containing aggregation-prone proteins, which were rarely observed in wild-type plants, were found to accumulate in nbr1 mutants under both control and heat stress conditions. Given that NBR1 co-localizes with these cytoplasmic puncta, we propose that Arabidopsis NBR1 is a plant aggrephagy receptor essential for maintaining proteostasis under both heat stress and non-stress conditions.